2019
DOI: 10.18632/aging.102402
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and phosphoproteome reveal mechanisms of action of atorvastatin against esophageal squamous cell carcinoma

Abstract: Statins comprise a class of prescription drugs used for reducing cholesterol. Evidence has also showed that statins could reduce cancer incidence. However, the anti-tumor mechanism of statins has not been fully defined. Here, we found that atorvastatin inhibited proliferation of esophageal squamous cell carcinoma (ESCC) cells. The underlying mechanisms were explored by mass spectrometry. The proteome data revealed that atorvastatin inhibited the cAMP and Rap1 signal pathways, except for Ras signal pathway. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Not only that, but there is a strong interest in reusing metformin to prevent cancer and cancer recurrence ( 22 ). Our recently study indicated atorvastatin, a lipid-lowering drug ( 23 ), and mefloquine, an anti-malarial drug ( 24 ), had a strong inhibitory effects on ESCC proliferation. Here, we screened the FDA-approved drug and found tegaserod maleate could inhibit proliferation of ESCC both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, but there is a strong interest in reusing metformin to prevent cancer and cancer recurrence ( 22 ). Our recently study indicated atorvastatin, a lipid-lowering drug ( 23 ), and mefloquine, an anti-malarial drug ( 24 ), had a strong inhibitory effects on ESCC proliferation. Here, we screened the FDA-approved drug and found tegaserod maleate could inhibit proliferation of ESCC both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Liquid chromatography with tandem mass spectrometryLC–MS/MS analysis was performed as previously described ( Chen et al, 2015 ; Yuan et al, 2019 ). Briefly, after the peptides were dissolved using 0.1% formic acid (FA), samples were separated using an EASY-nLC 1000 ultrahigh performance liquid phase system and then subjected to NSI source, followed by Q-Exactive Plus system analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Each well was then filled with 100 μL of fresh 1× PBS and high-content cell imaging analysis was used to photograph and analyze the number of cells. [18] 2.4 Cell Proliferation Assay KYSE150 (3.0×10 3 cells/well) and KYSE450 (4.0×10 3 cells/well) cells were seeded into a 96-well plate with 100 μL of complete growth medium (10% FBS) containing various concentrations of Arbidol (final concentration 0, 2.5, 5, 10, and 20 μM) and incubated at 37°C and 5% CO 2 for 24 h, 48 h, 72 h and 96h. The cells were fixed with 4% paraformaldehyde at room temperature for 30 min.…”
Section: Cell Toxicity Assaymentioning
confidence: 99%